'Primary care sensitive' situations that result in an ambulance attendance: a conversation analytic study of UK emergency '999' call recordings. Issue 11 (25th November 2018) - Booker, Matthew James; Shaw, Ali R G; Purdy, Sarah; Barnes, Rebecca
Abstract : Objectives: To explore common features of conversations occurring in a sample of emergency calls that result in an ambulance dispatch for a 'primary care sensitive' situation, and better understand the challenges of triaging this cohort. Design: A qualitative study, applying conversation analytic methods to routinely recorded telephone calls made through the '999' system for an emergency ambulance. Cases were identified by a primary care clinician, observing front-line UK ambulance service shifts. A sample of 48 '999' recordings were analysed, corresponding to situations potentially amenable to primary care management. Results: The analysis focuses on four recurring ways that speakers use talk in these calls. Progress can be impeded when call-taker's questions appear to require callers to have access to knowledge that is not available to them. Accordingly, callers often provide personal accounts of observed events, which may be troublesome for call-takers to 'code' and triage. Certain question formats—notably 'alternative question' formats—appear particularly problematic. Callers deploy specific lexical, grammatical and prosodic resources to legitimise the contact as 'urgent', and ensure that their perception of risk is conveyed. Difficulties encountered in the triage exchange may be evidence of misalignment between organisational and caller perceptions of the 'purpose' of the questions. Conclusions: Previous work has focused on exploring the presentation and triage of life-threatening medical emergencies. Meaningful insights into the challenges of EMS triage can also be gained by exploring calls for 'primary care sensitive' situations. The highly scripted triage process requires precise, 'codeable' responses to questions, which can create challenges when the exact urgency of the problem is unclear to both caller and call-taker. Calling on behalf of someone else may compound this complexity. The aetiology of some common interactional challenges may offer a useful frame for future comparison between calls for 'primary care sensitive' situations and life-threatening emergencies.